Warriors and Politicians - Stevenson, Charles A. (Cass Military Studies, 2006)
With historical case studies ranging from the Revolutionary War to the war in Iraq, this new book shows how and why the US military is caught between two civilian masters - the President and Congress - in responding to the challenges of warfighting, rearmament, and transformation. Charles Stevenson skilfully shows how, although the United States has never faced the danger of a military coup, the relations between civilian leaders and the military have not always been easy. Presidents have contended with military leaders who were reluctant to carry out their orders. Generals and Admirals have appealed to Congress for sympathy and support. Congressional leaders have tried to impose their own visions and strategies on the US armed forces. This triangular struggle has recurred time and again, in wartime and in efforts to reshape the military for future wars. Illustrating this dual system of civilian military control in a series of case studies, this new volume starts from the way the Continental Congress ran the Revolutionary War by committee and concludes with the George W. Bush and Donald Rumsfeld efforts to transform the US military into a modern terrorist-fighting force. This detailed coverage shows how warriors and politicians interacted at key points in US history. This book will be of great interest to all students of the US Military, government of the United States and of strategic and military studies in general.